Interpersonal Communication of Extension Kkbpk Towards Increasing Male Participation Post Modern Era in Parepare - Rusli, Rusli; Rustan, Ahmad Sultra (Al-Iftah: Journal of Islamic studies and society, 2021)
This thesis discusses how the interpersonal communication applied by the KKBPK extension workers in increasing the participation of men in the post-modern era towards family planning programs in the City of Parepare. The purpose of this thesis is to find out the planning and communication strategy between personal trainers of KKBPK to increase male participation, the obstacles that hinder male participation, and how the description of male participation in the post-modern era in Parepare City. This type of research is qualitative, field research (Field Research), researchers go directly to the field through observation, interviews, and documentation studies, in order to obtain clear and representative data. The results of this study indicate: (1) Interpersonal communication planning and strategy is the method used by the KKBPK Extension Officer in approaching men's participation, with interpersonal communication carried out face to face, it is easier for men to get and understand the family planning program messages conveyed. KKBPK instructor. (2) The obstacles that hinder the participation of men in the City of Parepare are the notion or perception that they still tend to hand over the responsibility for the family planning program entirely to their wives or women,psychological (worried about not optimal virility, impotence), social constraints (shame so gossip), wives who are not supportive on the grounds that the family planning program, especially vasectomy, opens up risky opportunities for men to cheat, with vasectomy it is feared that men will feel more free, "safe" -safe” if you have an affair, because the assumption is that the mistress will not get pregnant. (3) Various efforts have been made by the KKBPK Extension Officer, ranging from planning and strategy to formal (lurah, midwife) and informal (community leaders, religious leaders) approaches to increase the participation of men in the post-modern era in Parepare City.